A SUGGESTED ANALYTICAL SOLUTION TO DYNAMIC CHARACTERISTICS OF A PLATE DUE TO EFFECT THERMAL LOADING - A. Kareem, Husam; J. Jweeg, Muhsin; S. Hassan, Shaker (Journal of Engineering and Sustainable Development, 2016)
In order to find the effect of thermal loading on dynamic characteristics, a three-dimensional steady-state thermal analysis of a thin rectangular plate subjected to heat flux extending over a specific region with convection boundary conditions was conducted. An analytical solution was suggested with the intention of assuring the result, which was used to study the variation of dynamic characteristics. The derivation of a closed-form analytical solution of the heat equation for specific boundary conditions and heat flux model was necessary to describe the three-dimensional spatial temperature distributions which in turn were used to derive the required equation for the plate dynamics. Different plate dimensions were studied with heater location and shape was fixed, while its dimensions vary according to the plate dimension under consideration. The numerical and experimental results were found to be comparable.